The prognostic value of urinary chemokines at 6 months after pediatric kidney transplantation. (7th May 2018) - Mockler, Claire; Sharma, Atul; Gibson, Ian W.; Gao, Ang; Wong, Alexander; Ho, Julie; Blydt‐Hansen, Tom D.
Abstract: Pediatric kidney transplantation is lifesaving, but long‐term allograft survival is still limited by injury processes mediated by alloimmune inflammation that may otherwise be clinically silent. Chemokines associated with alloimmune inflammation may offer prognostic value early post‐transplant by identifying patients at increased risk of poor graft outcomes. We conducted a single‐center prospective cohort study of consecutive pediatric kidney transplant recipients (<19 years). Urinary CCL2 and CXCL10 measured at 6 months post‐transplant were evaluated for association with long‐term eGFR decline, allograft survival, and concomitant acute cellular rejection histology. Thirty‐eight patients with a mean age of 12.4 ± 4.6 years were evaluated. Urinary CCL2 was associated with eGFR decline until 6 months (ρ −0.43; P < .01), but not at later time points. Urinary CXCL10 was associated with eGFR decline at 36 months (ρ −0.49; P < .01), risk of 50% eGFR decline (HR = 1.04; P = .02), risk of allograft loss (HR = 1.05; P = .01), borderline rejection or rejection episodes 6‐12 months post‐transplant ( r .41; P = .02), and Banff i + t score ( r .47, P < .01). CCL2 and CXCL10 were also correlated with one another (ρ 0.54; P < .01). CCL2 and CXCL10 provide differing, but complementary, information that may be useful for early non‐invasive prognostic testing in pediatric kidney transplant recipients.